PERFORMANCE EVALUATION OF TURKISH RETAIL FIRMS USING THE FUZZY AHP, PROMETHEE, ELECTRE AND VIKOR METHODS - Bolukbas, Ufuk; Celik, Erkan; Guneri, Ali Fuat (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
The performance evaluation of firms determines capabilities of firms to compete in the sector and has a critical importance for the development of the sector. In this study, a fuzzy multi-criteria decision model is proposed to evaluate the performances of retail firms. The eight Turkish retail firms are analyzed and firms are evaluated in terms of ten different financial ratios in six separate groups. Fuzzy Analytic Hierarchy Process (FAHP), Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE), Elimination Et Choix Traduisant la Realit (ELECTRE) and Multicriteria Optimization and Compromise Solution (VIKOR) methods are integrated in the proposed model. A hierarchical model of financial performance evaluation is structured by the decision makers. FAHP is used to determine the weights of the criteria. These criteria weights and financial ratio values are input to the PROMETHEE, ELECTRE and VIKOR method to rank the firms. The rankings of methods are compared to each other's in the conclusion.
Keywords: DECISION-MAKING; Computer Science